Constructional Processing in a Second Language: The Role of Constructional Knowledge in Verb‐Construction Integration. Issue 4 (5th July 2019) - Kim, Hyunwoo; Rah, Yangon
Abstract: The constructionist approach holds that an argument structure construction, a conventionalized form–meaning correspondence of a sentence, allows language users to efficiently access sentential information. This study investigated whether increased sensitivity to constructional information would enable second language learners to efficiently fuse information from a verb and a construction during real‐time sentence processing. Based on their performance in an English sentence sorting task, we divided Korean‐speaking learners of English into construction‐centered and verb‐centered groups depending on their degree of reliance on constructional information in sorting. These groups were then administered a self‐paced reading task where learners read English constructions in a word‐by‐word fashion. Results showed that learners' reading time was contingent upon constructional sensitivity such that the construction‐centered group was faster than the verb‐centered group at integrating argument roles between a verb and a construction. These findings provide new evidence that constructional information can facilitate second language sentence processing. Abstract :